Cardiovascular risk factors as predictors of heart failure during hospitalization for Acute Coronary Syndromes. (11th May 2021) - Santos, H; Santos, M; Almeida, I; Miranda, H; Sa, C; Chin, J; Almeida, S; Sousa, C; Almeida, L
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: Portuguese Registry of Acute Coronary Syndromes Background: Cardiovascular risk factors (CVRF) are a growing health problem in developed countries. These patients have a higher prevalence of acute coronary syndromes (ACS) and as a consequence ACS complication, like heart failure (HF). HF after an ACS is a common complication and CVFR can influence its manifestation. Objective: Evaluate the impact of the CVRF in HF during the hospitalization for ACS. Methods: Multicenter retrospective study, based on the Portuguese Registry of ACS between 1/10/2010-4/09/2019. Patients were divided in two groups: A – without new onset of HF during the hospitalization for ACS and B – with new onset of HF during the hospitalization for ACS. CVFR was defined by body mass index, diabetes, arterial hypertension, smoking, neoplasia, dyslipidemia, coronary artery disease, chronic kidney disease and peripheral arterial disease. Logistic regression was performed to assess predictors of new onset HF in these patients. Results: 14717 patients were included, 2287 in group B (15.5%). Both groups were similar regarding body mass index (27.5 ± 4.3 vs 27.2 ± 4.4, p = 0.254). Curiously the group A exhibited higher prevalence of smoking status (29.8 vs 16.6%, p < 0.001). On the other hand, group B presented more females (25.0 vs 35.7%, p < 0.001), arterial hypertension (68.7 vs 78.2%, p < 0.001), diabetes mellitus (28.5 vs 43.1%, p < 0.001), dyslipidemia (62.2 vs 64.3%, p = 0.023), coronary artery disease (19.6 vs 25.6%, p < 0.001), neoplasia (4.4 vs 7.0%, p < 0.001), peripheral arterial disease (5.2 vs 15.8%, p < 0.001) and chronic kidney disease (4.6 vs 10.0%, p < 0.001). Logistic regression revealed that body mass index, diabetes, arterial hypertension, neoplasia and dyslipidemia were not predictors of HF during the hospitalization for ACS. Nevertheless, female gender (odds ratio (OR) 1.37, p < 0.001, confidence interval (CI) 1.22-1.54), chronic kidney disease (OR 1.59, p < 0.001, CI 1.33-1.90) and peripheral arterial disease (OR 1.54, p < 0.001, CI 1.27-1.86) were predictors of new onset of HF during hospitalization for ACS. Curiously, smoking seems to have a protective effect (OR 0.68, p < 0.001, CI 0.59-0.78) in new onset HF in ACS patients. Conclusions: Chronic kidney disease and peripheral arterial disease were predictors of new onset of HF in during hospitalization for ACS.